CURRENT LIMITING SWITCH OF ALTERNATIVE VOLTAGE - Bogusławski, Piotr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
Based on literature study of known thyristor limiters and the modification providing of a low current switch function was presented. The proposed DC/DC inverters for control and temperature indirect independency was described. Preliminary results of one phase switch circuit simulation are included. In summary succession problems of application was shortly pointed out.